Analisis Kepuasan Konsumen Terhadap Kualitas Pelayanan E-Commerce Jd.Id Menggunakan Metode E-Servqual (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
This study aims to determine which dimensions have a significant effect on customer satisfaction and to find out which service dimensions are the main priority to be improved using the E-Servqual method. The E-servqual method is the method used to measure the quality of services provided online. The dimensions of E-servqual that will be used in this research are system availability, fulfillment, efficiency, privacy, compensation, responsiveness, and contact. Collecting data in this study by distributing questionnaires with the respondent's criteria, namely JD.ID E-Commerce users. The results of this study indicate that the variables of efficiency, system availability, compensation, and responsiveness have a significant effect on JD.ID consumer satisfaction while fulfillment, privacy, and contact variables have no significant effect on JD.ID consumer satisfaction